Mask Detection Using Image Processing - Alvin Gusti Prabowo; Ardhi Fadli Firdaus; Gian Syahdatal Rizal (Universitas Komputer Indonesia, 2023)
In early 2020, the epidemic of a new type of pneumonia led by Wuhan, Hubei shocked the world, and then spread rapidly to more than 190 countries and regions. This outbreak is named Coronavirus Disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). The spread of this disease has widespread social and economic impacts. Therefore, during the current COVID-19 pandemic, regulations are enacted in which everyone is required to wear a mask and perform physical distancing when leaving the house in Indonesia to reduce the spread of COVID-19. The purpose of this study is to be able to create a detect the use of masks using deep learning methods with Alex net network type. The results showed that the development masks can be applied at the entrance of a mall or hospital by installing a detection device in front of the entrance. It can also be seen the results of the detection on a computer that has been integrated with the detection system. This research is useful to make it easier for people to wear masks or not and detect it automatically without having to do it manually by officers.